Insights into β-ketoacyl-chain recognition for β-ketoacyl-ACP utilizing AHL synthases. Issue 64 (20th July 2018) - Nhu Lam, Mila; Dudekula, Dastagiri; Durham, Bri; Collingwood, Noah; Brown, Eric C.; Nagarajan, Rajesh
Abstract : The design, synthesis and kinetic evaluation of beta-ketoacyl-ACP mimics for two 3-oxoacyl-ACP utilizing quorum signal synthases are reported. Abstract : Beta-ketoacyl-ACP utilizing enzymes in fatty acid, polyketide and acyl-homoserine lactone biosynthetic pathways are important targets for developing antimicrobial, anticancer and antiparasitic compounds. Published reports on successful isolation of beta-ketoacyl-ACPs in a laboratory remain scarce to date and thus most beta-ketoacyl-ACP utilizing enzymes are routinely characterized using small molecule substrates in lieu of the bonafide 3-oxoacyl-ACPs. We report the systematic investigation into the electronic, geometric and spatial aspects of beta-ketoacyl-chain recognition to develop 3-oxoacyl-ACP substrate mimics for two beta-ketoacyl-ACP utilizing quorum signal synthases.